EXPLORING THE ENERGY GENERATION POTENTIAL OF JATROPHA CAKE IN A BIOREFINERY: AN OPTIMIZATION STUDY - Nasir, Khadijah; Oyegoke, Toyese (JOURNAL OF ENGINEERING SCIENCE, 2025)
Waste management and energy access remain critical challenges globally, especially in developing countries where poor waste management and unreliable power supply exacerbate environmental and socio-economic issues. This study aims to explore the potential of using Jatropha cake as a sustainable bioenergy source in gas-turbine power plants to address these challenges. Using a Central Composite Design (CCD) approach, the study evaluates the effects of compressor efficiency, turbine efficiency, heat transfer coefficients, and heat transfer area on power generation from Jatropha cake, modeled using the DWSim simulation package. The findings show that an open-loop gas-turbine configuration with a compressor efficiency of 83.92% and turbine efficiency of 98% can generate a maximum power output of 174235 kW. In contrast, the closed-loop configuration, optimized with a heat exchanger (HX) at 120 W/m²K heat transfer coefficient and 1000 m² heat transfer area, yields 74375.70 kW. The results suggest that the open-loop configuration is more efficient, offering significantly higher power generation. This study highlights the viability of Jatropha cake as a bioenergy resource, providing a promising solution for improving power supply in energy-deficient communities while contributing to sustainable waste management practices.